Family help received by Mexican older adults across socioeconomic strata: changes over a critical decade - Karina Orozco-Rocha; Cesar Gonzalez-Gonzalez; Rebeca Wong (Pan American Health Organization, 2021)
Objective. To identify how patterns of family economic support help alleviate the cumulative effects of inequality, with focus on the financial support that children give their elderly parents. Methods. This paper uses data from two cross-sections, 2001 and 2012, of the Mexican Health and Aging Study for the 50 years and older population. Analysis includes descriptive statistics to estimate differences in economic support based on family and individual characteristics; and a multinomial probit regression model, in each cross-section, to analyze the amount of money received for economic help and the associated characteristics. Results. Economic help received was significantly reduced, both in proportion, from 20% to 10% between 2001 and 2012, and in the amount received, with differences by income quintile. In 2001, 14.9% of those in the lowest quintile (Q1) would move to Q4-Q5 with children's help; in 2012, this was 9.1%. The adjusted probability of receiving any amount of money from children decreased from 0.511 in 2001 to 0.340 in 2012. Conclusions. In Mexico, economic inequality in the 50 years and older population remains a constant. Economic help received from children varied by income quintile and plays an important role for those in the lowest income groups. More research is needed to understand the patterns of intergenerational exchanges as these cohorts of older adults continue to age and as future cohorts are entering old age with more pronounced changes than the current cohorts experienced over this critical decade.